America's Hundred Years' War : U.S. Expansion to the Gulf Coast and the Fate of the Seminole, 1763-1858 - Belko, W. Stephen, 1967- (Book collections on Project MUSE., 2011)
Featuring essays on topics ranging from international diplomacy to Seminole military strategy, the volume urges us to reconsider the reasons for and impact of early U.S. territorial expansion. It highlights the actions and motivations of Indians and African Americans during the period and establishes the groundwork for research that is more balanced and looks beyond the hopes and dreams of whites.